The Mathematical Reasoning Ability of Highly-Skilled Primary School Students in the Context of Eco-Mathematics - Dwimartin Bella Hapsari Bella; Feny Rita Fiantika Feny (Universitas Pendidikan Ganesha, 2024)
Mathematical reasoning is one of the essential skills in mathematics learning; however, many students still struggle to apply it, particularly in real-life contexts. This study aims to describe the extent to which fifth-grade students (V-B) can apply mathematical reasoning in solving multiplication problems presented within an eco-mathematics context. Furthermore, this study seeks to highlight the relationship between mathematics and eco-mathematics (economy, culture, and objects of mathematics), which can be utilized as a learning resource in teaching decimal number multiplication. This research employs a qualitative method with an exploratory descriptive approach to provide an in-depth and structured description of the findings from the written test on students' mathematical reasoning abilities. Data collection techniques include a written mathematical reasoning test, interviews, observations, and documentation. Data analysis is conducted through credibility testing, dependability testing, transferability testing, and confirmability testing. The findings indicate that students with high mathematical ability actively engage in answering questions during classroom learning and are able to explore their reasoning skills by discovering new concepts. Thus, the eco-mathematics approach can serve as an effective instructional strategy to enhance students' mathematical reasoning skills in understanding decimal number multiplication.